X-Ray Polarization of the High-synchrotron-peaked BL Lac H 1426+428 - Xin-Ke Hu; Jia-Xuan Li; Yu-Wei Yu; Ji-Shun Lian; Wei Deng; Hai-Ming Zhang; Jin Zhang (The Astrophysical Journal)
We report the X-ray polarization properties of the high-synchrotron-peaked BL Lac H 1426+428, based on two-epoch observational data from the Imaging X-ray Polarimetry Explorer (IXPE). For the first observation, only an upper limit of polarization degree (Π _X ), Π _X  < 19.5%, at the 99% confidence level (CL) is determined. In contrast, for the second observation, we derive Π _X  = 20.6% ± 2.9% with a polarization angle ( ψ _X ) of ψ _X  = 116 $\mathop{.}\limits^{\unicode{x000b0}}$ 1 ± 4 $\mathop{.}\limits^{\unicode{x000b0}}$ 1 at a CL of 7.1 σ . The time-resolved and energy-resolved polarization analysis reveals no significant variation in ψ _X and no detectable polarization within narrower energy bins for the first observation, while the polarization during the second observation is dominated by low-energy photons. Furthermore, the X-rays during the second observation are found to be in a higher flux state with a harder spectrum compared to that observed during the first observation, consistent with a harder-when-brighter behavior. We propose that the enhanced X-ray emission observed during the second observation is produced by shock-accelerated electrons within an ordered magnetic field region via synchrotron radiation. Nonetheless, no significant detection of polarization during the first IXPE observation may be due to the limited number of detected photons.